Isoniazid-induced Encephalopathy in a Patient with Pott’s Disease with Chronic Kidney Disease: A Case Report (Journal of Rangpur Medical College, 2023)
We report an isoniazid-induced encephalopathy in a man with chronic renal failure. Drug-induced encephalopathy is a common side effect of many drugs. Isoniazid (INH), a first-line drug for tuberculosis, can cause encephalopathy in patients with chronic kidney disease (CKD). For Pott's disease of the thoracic spine, he received rifampicin, INH, pyrazinamide, and ethambutol with pyridoxine and prednisolone. But the patient is free of pyridoxine for two and a half months. Subsequently, after treatment, the patient experienced recurrent episodes of altered consciousness, irrelevant conversations, and disorientation. After ruling out other causes, isoniazid-induced encephalopathy was suspected and confirmed by improvement of symptoms after discontinuation of high-dose isoniazid and pyridoxine.J Rang Med Col. March 2023; Vol. 8, No. 1:72-75